Factors Affecting Middle School Teachers’ Attitudes Toward the Inclusion of Students With Disabilities - Aldosari, Mubarak S. (Frontiers in Psychology, 2022)
Teachers’ positive attitudes are an essential element for the successful inclusion of students who have disabilities in schools with their peers who do not have disabilities. The current quantitative study examines middle school teachers’ attitudes toward the inclusion of students with disabilities in regular schools in Saudi Arabia and the factors that affect their attitudes. Middle school teachers (N = 613) from schools in Riyadh responded to a questionnaire regarding their opinions relative to the integration of students with disabilities. The results indicate that middle school teachers have a neutral attitude toward the inclusion of students with disabilities in regular schools. Moreover, teacher-related factors such as gender, position, and experience do not affect teacher attitudes toward inclusion. In contrast, training in inclusion plays a significant role in middle school teachers’ attitudes toward inclusion of students with disabilities. The implications of the results and suggestions for further research are discussed in the study.